Anticancer diiron aminocarbyne complexes with labile N-donor ligands - Stocchetti, Sara; Vančo, Ján; Bresciani, Giulio; Biancalana, Lorenzo; Belza, Jan; Zacchini, Stefano; Dvořák, Zdeněk; Benetti, Sara; Biver, Tarita; Bortoluzzi, Marco; Trávníček, Zdeněk; Marchetti, Fabio (European journal of medicinal chemistry, 2025)
The novel diiron amine complexes [Fe2Cp2(CO)(NH2R')(μ-CO){μ-CN(Me)(Cy)}]CF3SO3 [R' = H, 3; Cy, 4; CH2CH2NH2, 5; CH2CH2NMe2, 6; CH2CH2(4-C6H4OMe), 7; CH2CH2(4-C6H4OH), 8; Cp = η5-C5H5, Cy = C6H11 = cyclohexyl] were synthesized in 49-92 % yields from [Fe2Cp2(CO)2(μ-CO){μ-CN(Me)(Cy)}]CF3SO3, 1a, using a straightforward two-step procedure. They were characterized by IR and multinuclear NMR spectroscopy, and the structure of 7 was confirmed through X-ray diffraction analysis. Complexes 3-8 and the acetonitrile adducts [Fe2Cp2(CO)(NCMe)(μ-CO){μ-CN(Me)(R)}]CF3SO3 (R = Cy, 2a; Me, 2b; Xyl = 2,6-C6H3Me2, 2c) were assessed for their water solubility, octanol-water partition coefficient and stability in physiological-like solutions. The in vitro antiproliferative activity of 2a-c and 3-8 was tested on seven human cancer cell lines (A2780, A2780R, PC3, A549, MCF7, HOS and HT-29), while the selectivity was evaluated using normal MRC-5 cells. Overall, the complexes exhibited variable cytotoxicity, with IC50 values reaching the low micromolar range for 3, 7 and 8 in A2780 and A2780R cells, along with significant selectivity. Targeted experiments covered cell cycle modification, induction of cell death, mitochondrial membrane potential, ROS production and interaction with DNA and bovine serum albumin (BSA) as a model protein. The interaction of 3 with BSA was further investigated through computational studies. Results showed a negligible increase in intracellular ROS levels (except for 2b) and insignificant changes in mitochondrial membrane potential.
Keywords: železo; Ligands; Drug Screening Assays, Antitumor; Humans; Iron; ligandy; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; komplexní sloučeniny; Labile ligand; Diiron complexes; Dose-Response Relationship, Drug; In vitro cytotoxicity; Antineoplastic Agents; lidé; aminy; zvířata; proliferace buněk; Coordination Complexes; molekulární struktura; Molecular Structure; Cellular effects; Amines; Cell Proliferation; screeningové testy protinádorových léčiv; nádorové buněčné linie; protinádorové látky; vztah mezi dávkou a účinkem léčiva; Animals; Cell Line, Tumor; Bioorganometallic chemistry